2015
DOI: 10.1177/0363546515576127
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Involved and Uninvolved Limb Function During Rehabilitation After Anterior Cruciate Ligament Reconstruction

Abstract: During ACL reconstruction rehabilitation, LSI improvements indicated absolute increases in involved limb ability and were not attributable to uninvolved limb deterioration. The single-leg squat, retro step-up, single-leg hop, crossover triple hop, and timed hop are suggested as highly useful tests, since all showed initial LSI below 90%, with significant LSI improvement after rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 39 publications
2
74
0
3
Order By: Relevance
“…Our results seem to be consistent with those reported by other authors [14, 15], showing symmetry restoration and functional recovery before and after ACLR in gait, sprint and single-leg hop tests. However, we were not able to observe this phenomenon in all tests performed, since both the drop vertical jump and the vertical hop test did not improve their LSI after ACLR.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results seem to be consistent with those reported by other authors [14, 15], showing symmetry restoration and functional recovery before and after ACLR in gait, sprint and single-leg hop tests. However, we were not able to observe this phenomenon in all tests performed, since both the drop vertical jump and the vertical hop test did not improve their LSI after ACLR.…”
Section: Discussionsupporting
confidence: 93%
“…However, we were not able to observe this phenomenon in all tests performed, since both the drop vertical jump and the vertical hop test did not improve their LSI after ACLR. Logerstedt et al [15] evaluated functional recovery (quadriceps strength testing, hop testing, and self-reported questionnaires for knee function) in eighty-three athletes after an ACL injury, and at different times after ACLR. They concluded that limb to limb asymmetries are reduced, and normal limb symmetry is returned to a similar level 6 months after ACLR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent study described a pattern of improvement in the uninvolved limb that must be accounted for when measuring progress during post-operative rehabilitation; in addition we identified the tests within the functional test battery that demonstrated the most significant changes over time [1].…”
Section: Introductionmentioning
confidence: 99%
“…71 Quadriceps strength of the ACLR limb is often evaluated in comparison to the contralateral limb for a measure of limb symmetry index. 24,168 Quadriceps strength asymmetry is present after initial ACL injury and increases six months after reconstruction. 45,97 Deficits in quadriceps strength symmetry are present in both isometric and isokinetic movements.…”
Section: 137mentioning
confidence: 99%